The Impact Of Smartphone Use On Social Interaction In The Work Environment: Case Study Of Pt Teodore Pan Garmindo Tasikmalaya Employees - Pirdaus, Dede Irman; Amal, Moh Alfi; kalfi (Communication In Research And Publications, 2024)
This research aims to evaluate the impact of the use of communication technology, especially smartphones, on social interactions in the work environment. Data was collected through a survey filled out by 150 employees from Pt Teodore Pan Garmindo Tasikmalaya. The results of the analysis show that smartphone use has the potential to influence social interactions, especially in the context of face-to-face communication. Women tend to be more involved in social interactions via smartphones compared to men. These findings emphasize the importance of controlling smartphone use wisely in social interaction situations. Effective face-to-face communication remains the key to building harmonious relationships in the work environment.